Correlation Between Serum Ferritin and Testosterone Level in Adolescent Male with Transfusion Dependent Thalassemia - Raja Iqbal Mulya Harahap; Nina Tristina; Delita Prihatni; Dewi Kartika Turbawaty (Faculty of Medicine, Universitas Padjadjaran, 2021)
Transfusion-dependent thalassemia (TDT) is a type of beta-thalassemia that needs regular and long-term blood transfusions. Complications can occur due to the deposition of iron in TDT patients, including endocrine complications causing deficiency of testosterone that plays a role in the secondary sexual development in males. The objective of this study was to understand the correlation between ferritin and testosterone level in male adolescences with transfusion-dependent thalassemia. This cross-sectional observational correlative study was conducted from April to August 2019 on 74 males aged 12-18 years old who were presented to the Thalassemia Outpatient clinic, Dr. Hasan Sadikin General Hospital, Bandung. Blood was collected using phlebotomy for ferritin and total testosterone serum examination. Data were then analyzed using SPSS version 17.0. Low testosterone level (<3.0 ng/mL) was found in 63.5% of subjects. Results of the Spearmen correlation test demonstrated a negative correlation with r: -0,699 and p-value <0.001, showing a negative, strong, and significant correlation among those variables. The higher ferritin level in TDT patients indicates a high level of the free iron level in the body that can destroy the endocrine organs and cause deprivation of testosterone secretion, leading to hypogonadism in transfusion dependent thalassemia patients.